Annotated list of Euphorbiaceae species for Quindío (Revista de Investigaciones Universidad del Quindío, 2010)
We present an annotated list for all species of Euphorbiaceae that occurs in department of Quindío. We revised and determined 423 specimens from the Herbarium collection of University of Quindío (HUQ).  For Quindio we found that Euphorbiaceae is represented by 16 genera: Euphorbia and Acalypha as the major genus with 9 and 7 species respectively, followed by Croton (5 spp), Dalechampia (3 spp), Alchornea (2 spp), Mabea (2 spp), Jatropha (2 spp) and Chamaesyce (2 spp), and 8 monospecific genus, Ricinus, Dysopsis, Tetrorchidium, Manihot, Codiaeum, Caperonia, Plukenetia and Sapium. In was found 40 species in total, of which 14 were new reports for Quindío: Dalechampia canescens, D. cissifolia, Plukenetia volubilis and Croton xalapensis, the latter is a new report for Colombia. We confirmed the presence of Acalypha platyphylla and A. setosa and we also identified A. diversifolia, A. macrostachya and Euphorbia heterophylla as species with wide distribution based on findings in 12 localities of Quindío; in contrast, Dalechampia canescens, Dysopsis paucidentata and Euphorbia peplus only were found in one or two localities.
Keywords: Euphorbiaceae; flora; taxonomy; Quindío; Colombia; South America; annotated list